Induction of mitophagy-mediated antitumor activity with folate-appended methyl-β-cyclodextrin - Kameyama K (Dove Medical Press, 2017)
Kazuhisa Kameyama,1,* Keiichi Motoyama,1,* Nao Tanaka,1 Yuki Yamashita,1 Taishi Higashi,1 Hidetoshi Arima1,2,* 1Department of Physical Pharmaceutics, Graduate School of Pharmaceutical Sciences, 2Program for Leading Graduate Schools “HIGO (Health Life Science: Interdisciplinary and Glocal Oriented) Program,” Kumamoto University, Kumamoto, Japan *These authors contributed equally to this work Abstract: Mitophagy is the specific autophagic elimination system of mitochondria, which regulates cellular survival via the removal of damaged mitochondria. Recently, we revealed that folate-appended methyl-β-cyclodextrin (FA-M-β-CyD) provides selective antitumor activity in folate receptor-α (FR-α)-expressing cells by the induction of autophagy. In this study, to gain insight into the detailed mechanism of this antitumor activity, we focused on the induction of mitophagy by the treatment of FR-α-expressing tumor cells with FA-M-β-CyD. In contrast to methyl-β-cyclodextrin, FA-M-β-CyD entered KB cells, human epithelial cells from a fatal cervical carcinoma (FR-α (+)) through FR-α-mediated endocytosis. The transmembrane potential of isolated mitochondria after treatment with FA-M-β-CyD was significantly elevated. In addition, FA-M-β-CyD lowered adenosine triphosphate (ATP) production and promoted reactive oxygen species production in KB cells (FR-α (+)). Importantly, FA-M-β-CyD enhanced light chain 3 (LC3) conversion (LC3-I to LC3-II) in KB cells (FR-α (+)) and induced PTEN-induced putative kinase 1 (PINK1) protein expression, which is involved in the induction of mitophagy. Furthermore, FA-M-β-CyD had potent antitumor activity in BALB/c nu/nu mice xenografted with KB cells (FR-α (+)) without any significant side effects. Taken together, these findings demonstrate that the autophagic cell death elicited by FA-M-β-CyD could be associated with mitophagy induced by an impaired mitochondrial function. Keywords: mitophagy, autophagy, folate receptor, methyl-β-cyclodextrin, tumor targeting